The kid-friendly ADHD & autism cookbook : the ultimate guide to the gluten-free, milk-free diet - Compart, Pamela J.; Laake, Dana Godbout (Beverly, Mass. : Fair Winds Press, 2012)
Containing the best kid-friendly recipes, this is a complete, new-in-paperback guide to the gluten-free, milk-free diet for ADHD and autism. In addition to current research and findings, this book provides recommendations from the authors for packing school lunches and snacks, plus hundreds of recipes. One of the challenges that parents face is coping with children who have picky appetites and crave the very foods that affect their behavior, focus, and development. The other challenge is finding ways to get their children to eat healthy foods and improve their nutritional status. The uniqueness of this book is that it not only provides gluten-free milk-free substitutes and recipes, it provides successful suggestions for feeding the picky eater. The authors share details about just how and why the diet works. The specialty ingredients are explained and extensive sources provided. There are also testimonials from the parents and from the children themselves.
Get ready! Get set! Food reactions : what they are and how to test for them ; The culprits : glutens, casein, soy, and others ; More culprits ; Eater beware! : improving your nutritional IQ and shooting down myths ; Yes, there is plenty left to eat! ; Getting started and bumps along the way ; Dealing with the diet and common concerns ; A complete guide to making breakfast and packing lunches -- go! The kid-friendly recipes. Introduction to recipes ; Beverages and healthy shakes ; Condiments, dressings, and sauces ; Breads, muffins, waffles, and pancakes ; Main dishes and one-dish meals ; Rice and beans ; Vegetables and side dishes ; Salads ; Soups and stews ; Fruits, sweets, and treats -- Appendix. Resources.
Includes bibliographical references (p. 329-333) and index.
Keywords: Autism -- Diet therapy -- Recipes; Attention-deficit hyperactivity disorder -- Diet therapy -- Recipes; Gluten-free diet -- Recipes; Autism -- Diet therapy; Attention-deficit hyperactivity disorder -- Diet therapy; Gluten-free diet; Casein-free diet; Cooking for children with disabilities; Cookbooks; Cookbooks